Characterization of Bambara nut shell ash (BNSA) in concrete production - Uwadiegwu, Alaneme George; Michael, Mbadike Elvis (Penerbit Universiti Kebangsaan Malaysia, 2021)
The goal of achieving concrete with adequate durability properties in terms of reduced susceptibility to alkali-silica and mechanical-strength behaviour has led to several high-performance materials development. While the use of Bambara nut shell ash in concrete is gaining acceptance in various applications, the mineralogical composition of such by-product materials cannot be easily controlled as a manufactured pozzolan. In this research work, the characterization and use of BNSA in concrete production was investigated. A mix proportion of 1:3:6 with water cement ratio of 0.55 were used. The percentage replacement of cement with BNSA from 0-40%. Concrete cubes of 150mm × 150mm × 150mm of OPC/BNSA were cast and cured at 3, 7, 28, 60 and 90 days respectively. At the end of each period of hydration, three replicate concrete samples for each period of hydration were crushed and their average comprehensive strength recorded. The result for the compressive strength test indicated rise in percentage difference as the BNSA replacement ratio increases from 5% to 40% with a value of 20.69% to 46.53% respectively. The concrete density response showed slight increment in percentage difference with a value of 0.85% to 3.47% for BNSA replacement ratio of 5% to 40% respectively. The Poisson ratio test results obtained indicates percentage difference increase as the BNSA ratio increases from 5% to 40% with a value of 5.17% to 11.14% respectively. Furthermore, the young’s modulus of elasticity results obtained showed percentage difference rise from 9.4% to 14.17% as BNSA ratio increases from 10.81% to 29.412% as BNSA replacement ratio increases from 5% to 40% respectively. The results indicate satisfactory performance at 5% replacement.